2017
DOI: 10.4103/jpi.jpi_34_17
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Classification of Colorectal Polyps on Whole-slide Images

Abstract: Context:Histopathological characterization of colorectal polyps is critical for determining the risk of colorectal cancer and future rates of surveillance for patients. However, this characterization is a challenging task and suffers from significant inter- and intra-observer variability.Aims:We built an automatic image analysis method that can accurately classify different types of colorectal polyps on whole-slide images to help pathologists with this characterization and diagnosis.Setting and Design:Our meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 273 publications
(132 citation statements)
references
References 42 publications
2
128
0
2
Order By: Relevance
“…Our study not only demonstrates the utility of a deep learning model for classification of colorectal polyps but also advances previous literature in terms of model evaluation and study design. The previous foremost study on deep learning for colorectal polyp classification, done by our team, 26,27 demonstrated good performance on an internal dataset but used a simpler approach and did not include pathologist-level performance or local diagnoses. Our study, on the other hand, evaluates a deep neural network on a multi-institutional external dataset and demonstrates a comparable diagnostic performance of deep neural networks compared to local pathologists at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study not only demonstrates the utility of a deep learning model for classification of colorectal polyps but also advances previous literature in terms of model evaluation and study design. The previous foremost study on deep learning for colorectal polyp classification, done by our team, 26,27 demonstrated good performance on an internal dataset but used a simpler approach and did not include pathologist-level performance or local diagnoses. Our study, on the other hand, evaluates a deep neural network on a multi-institutional external dataset and demonstrates a comparable diagnostic performance of deep neural networks compared to local pathologists at the point-of-care.…”
Section: Discussionmentioning
confidence: 99%
“…Among feature learning methods, deep learning and, more specifically, Convolutional Neural Networks (CNNs) have now become a major trend in many computer vision and medical tasks [10][11][12]. In CNNs, a number of convolutional and pooling layers learn by backpropagation the set of features that are best for classification, thus avoiding the design of handcrafted texture descriptors.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial intelligence, and specifically deep learning, is now being applied to the fields of clinical dermatology and pathology. [ 39 40 41 42 43 44 45 46 47 48 ] Both specialties are image intense, rely on the integration of visual skills for diagnosis, and are a natural segue for algorithmic development. Esteva et al .…”
Section: Discussionmentioning
confidence: 99%